Analisi Data Transaksi Penjualan Menggunakan Algoritma Apriori Untuk Menentukan Paket Promosi Refarasi Mobil - R, Aria Renalda; Irawan, Agung Susilo Yuda; Suharso, Aries (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Rizal Motor Workshop is a business in the field of services and sales of auto parts. More and more workshops are growing rapidly at this time, making Rizal Motor Workshop making a better marketing strategy than other workshops. With a promotional package it will attract the attention of consumers who were previously not interested in shopping to become very interested because of the available promotional packages. To determine the promotional package at the Rizal Motor Workshop to be more efficient and on target, the author uses one way to look at the items most frequently purchased by consumers. The purpose of this study is to analyze sales transaction data to be used as a promotional package based on the buying patterns of consumers. The method used in this study uses the Knowledge Discovery in Database (KDD) method which consists of stages of data selection, data cleaning, data transformation, data mining, and evaluation. The algorithm in this study uses the Apriori Algorithm which looks at the itemset formed, in this study using 4 itemsets with a minimum support of 60% and a minimum confidence of 90%. For the results obtained are associations between products or connectedness of goods, in this study the confidence value obtained was 98.182% which is the best confidence value contained in the 3 itemse.